Evaluation of the synergistic antifungal activity of micafungin and voriconazole plus sertraline against Candida auris - Alanís Ríos, Sergio Armando; González, Gloria M.; Andrade, Ángel; Becerril García, Miguel A.; Bonifaz, Alexandro; Robledo Leal, Efrén Ricardo; Montoya, Alexandra M.; Treviño Rangel, Rogelio de Jesús (Sociedade Brasileira de Microbiologia, 2022)
Candida auris is an emerging global public health threat. It is an opportunistic yeast that usually affects critically ill patients in healthcare settings and is characterized by reduced susceptibility to multiple antifungal classes. Combination therapy with antifungals and repurposed drugs is a feasible alternative to overcome this problem. The aim of this study was to examine the in vitro interactions and potential synergy of micafungin (MFG) and voriconazole (VRC) plus the antidepressant sertraline (SRT) against clinical isolates of C. auris. Conventional antifungal testing was first performed with the three drugs according to the CLSI methodology. Drug interactions were determined by the checkerboard microdilution assay using the fractional inhibitory concentration (FIC) index. Synergistic interactions were noted with the combination of MFG and SRT plus VRC with FIC values of 0.37 to 0.49 for some strains. Indiferent interactions were observed when MFG was combined with SRT with just one exception (FIC 0.53). No antagonism was observed for any combination. The combination of VRC with MCF or SRT may be relevant for treating C. auris infections.